-14+6x+7=2x+1+5x

Simple and best practice solution for -14+6x+7=2x+1+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14+6x+7=2x+1+5x equation:


Simplifying
-14 + 6x + 7 = 2x + 1 + 5x

Reorder the terms:
-14 + 7 + 6x = 2x + 1 + 5x

Combine like terms: -14 + 7 = -7
-7 + 6x = 2x + 1 + 5x

Reorder the terms:
-7 + 6x = 1 + 2x + 5x

Combine like terms: 2x + 5x = 7x
-7 + 6x = 1 + 7x

Solving
-7 + 6x = 1 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-7 + 6x + -7x = 1 + 7x + -7x

Combine like terms: 6x + -7x = -1x
-7 + -1x = 1 + 7x + -7x

Combine like terms: 7x + -7x = 0
-7 + -1x = 1 + 0
-7 + -1x = 1

Add '7' to each side of the equation.
-7 + 7 + -1x = 1 + 7

Combine like terms: -7 + 7 = 0
0 + -1x = 1 + 7
-1x = 1 + 7

Combine like terms: 1 + 7 = 8
-1x = 8

Divide each side by '-1'.
x = -8

Simplifying
x = -8

See similar equations:

| by=a+x | | yb=x+a | | -2(7x-1)+7=-14x+9 | | (4+9i)+(5-8i)= | | 3(4x-2)=-2(-6x+3) | | 10m^2=2m+3.14159 | | 8=-7x+4+2 | | 2(15d+45c)+5/6(12d+18c) | | 5*-1+4*5= | | 16=4x-5 | | -2k^2+72=0 | | y-12=0.666(x-6) | | -4x-1/2y=10 | | -7=4r | | 3c-2d=2 | | 3/4x-5-7/3x-1 | | 3b^1/2(2b^1/2+5b^3/2) | | 5(2x+8x)=0 | | 3x+5=12x-20 | | 3=2c-11 | | -d+-18=0 | | 1566-853= | | x*13+15=x*5+207 | | 3x-2/7=-45 | | 3.42-6.3x+1.11=22.8 | | -77-7x=9x+15 | | -2(3x+4)-2=12x-6(3x+2) | | 8y-20=0 | | 3x+2+5x=2x+4+7.3x | | 7x-10/2=-26 | | 2s+7/5=9 | | 1/2x=7/10x+3/5 |

Equations solver categories